Potential Distribution Map of Culicoides insignis (Diptera: Ceratopogonidae), Vector of Bluetongue Virus, in Northwestern Argentina. Issue 1 (1st July 2016) - Veggiani Aybar, Cecilia A.; Díaz Gomez, Romina A.; Dantur Juri, María J.; Lizarralde de Grosso, Mercedes S.; Spinelli, Gustavo R.
Abstract: Culicoides insignis Lutz is incriminated as a vector of bluetongue virus (BTV) to ruminants in America. In South America, almost all countries have serological evidence of BTV infections, but only four outbreaks of the disease have been reported. Although clinical diseases have never been cited in Argentina, viral activity has been detected in cattle. In this study, we developed a potential distribution map of Culicoides insignis populations in northwestern Argentina using Maximum Entropy Modeling (Maxent). For the analyses, information regarding both data of specimen collections between 2003 and 2013, and climatic and environmental variables was used. Variables selection was based on the ecological relevance in relation to Culicoides spp. biology and distribution in the area. The best Maxent model according to the Jackknife test included 53 C. insignis presence records and precipitation of the warmest quarter, altitude, and precipitation of the wettest month. Accuracy was evaluated by the area under the curve (AUC = 0.97). These results provide an important analytical resource of high potential for both the development of suitable control strategies and the assessment of disease transmission risk in the region.